Analysis of the Payroll System to Achieve the Principle of Justice in the Furniture Business of CV Surya Utama Bone from the Perspective of Islamic Accounting - Raodatul Janna; Abdulahana; Ismail Keri (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the payroll system of the furniture business CV Surya Utama Bone from the perspective of Islamic accounting, particularly in applying the principle of justice. The background of this research is rooted in the importance of integrating Islamic values into profit distribution practices, in contrast to conventional systems that tend to prioritize capital owners. The study adopts a descriptive qualitative approach to gain a deep understanding of profit-sharing practices based on the direct experiences of the research subjects. Data collection techniques include observation, in-depth interviews, and documentation. The data analysis process involves data reduction, data presentation, and drawing conclusions. The findings reveal that: (1) the profit-sharing system at CV Surya Utama is implemented fairly based on mutual agreement between the owner and employees, with allocations made for reinvestment, operational needs, and reserves; (2) the profit distribution practices reflect the core principles of Islamic accounting, free from elements of usury (riba), uncertainty (gharar), and injustice. In conclusion, the payroll system applied by CV Surya Utama aligns with the principles of justice and transparency in Islamic accounting, while also contributing to the sustainability of the business and enhancing the motivation of all stakeholders involved.